Supplemental Citrulline Is More Efficient Than Arginine in Increasing Systemic Arginine Availability in Mice(1)(2)(3) - Agarwal, Umang (J Nutr, 2017)
Background: Arginine is considered to be an essential amino acid in various (patho)physiologic conditions of high demand. However, dietary arginine supplementation suffers from various drawbacks, including extensive first-pass extraction. Citrulline supplementation may be a better alternative than arginine, because its only fate in vivo is conversion into arginine. Objective: The goal of the present research was to determine the relative efficiency of arginine and citrulline supplementation to improve arginine availability. Methods: Six-week-old C57BL/6J male mice fitted with gastric catheters were adapted to 1 of 7 experimental diets for 2 wk. The basal diet contained 2.5 g l-arginine/kg, whereas the supplemented diets contained an additional 2.5, 7.5, and 12.5 g/kg diet of either l-arginine or l-citrulline. On the final day, after a 3-h food deprivation, mice were continuously infused intragastrically with an elemental diet similar to the dietary treatment, along with l-[(13)C(6)]arginine, to determine the splanchnic first-pass metabolism (FPM) of arginine. In addition, tracers were continuously infused intravenously to determine the fluxes and interconversions between citrulline and arginine. Linear regression slopes were compared to determine the relative efficiency of each supplement. Results: Whereas all the supplemented citrulline (105% ± 7% SEM) appeared in plasma and resulted in a marginal increase of 86% in arginine flux, supplemental arginine underwent an ∼70% FPM, indicating that only 30% of the supplemental arginine entered the peripheral circulation. However, supplemental arginine did not increase arginine flux. Both supplements linearly increased (P < 0.01) plasma arginine concentration from 109 μmol/L for the basal diet to 159 and 214 μmol/L for the highest arginine and citrulline supplementation levels, respectively. However, supplemental citrulline increased arginine concentrations to a greater extent (35%, P < 0.01). Conclusions: Citrulline supplementation is more efficient at increasing arginine availability than is arginine supplementation itself in mice.